Analysis of the Efficiency and Marketing Channels for Robusta Coffee Beans (Coffea Robusta) in Pulau Village, Pajar Bulan Subdistrict, Lahat - Iskandar Iskandar; Indra Hartini (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to determine the efficiency of the marketing channels for Robusta coffee beans. It seeks to identify the marketing costs, profits, marketing margins, and marketing efficiency of coffee in Pulau Village, Pajar Bulan Subdistrict, Lahat Regency. This study employs a survey method using questionnaires administered to respondents. There are two marketing channels in Pulau Village. In Marketing Channel I, the marketing entities involved are farmers and wholesalers. In Marketing Channel II, the marketing entities involved are farmers, small retailers, and wholesalers. Marketing Channel I is more efficient than Marketing Channel II because it has a lower margin. With a lower margin, the share received by farmers is higher. In Channel I, the marketing margin is Rp. 1,000.00, and the Farmer’s Share is 97.45%. In Channel II, the marketing margin is Rp. 2,000.00 and the Farmer’s Share is 94.96%. The research findings indicate that Marketing Channel I is shorter than Marketing Channel II, and the Farmer’s Share is higher in Channel I than in Channel II.